2001
DOI: 10.1054/bjoc.2000.1589
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor β expression and depth of myometrial invasion in human endometrial cancer

Abstract: SummaryWe assessed the relative expression of oestrogen receptor (ER)α and oestrogen receptor (ER)β mRNAs in 36 human endometrial cancers using a multiplex polymerase chain reaction (PCR). To determine whether or not the expression of ER subtypes in endometrial cancers is associated with clinicopathological parameters, we examined correlations between ER subtypes and age, tumour grade and depth of myometrial invasion. Using multiple regression analysis, myometrial invasion showed a significant correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 18 publications
0
10
1
1
Order By: Relevance
“…Overall, the inconsistencies observed with MI may be due to differences in stage or grade amongst selected patients and the various definitions of MI; depths of >1/3 (26), >50% (22) and ≥66% (18) are all regarded as cut-off values for deep MI in various studies, indicating that in endometrial cancer, the depth of MI has various roles according to the severity of the disease. In previous studies MI has been associated with certain biochemical indicators, including levels of free insulin-like growth factor-1 plasma (27), nucleoporin (88kDa)-mRNA expression (28) and endoplasmic reticulum-β (29). An association was also demonstrated between tumor-associated macrophages and depth of MI (30).…”
Section: A B Cmentioning
confidence: 87%
“…Overall, the inconsistencies observed with MI may be due to differences in stage or grade amongst selected patients and the various definitions of MI; depths of >1/3 (26), >50% (22) and ≥66% (18) are all regarded as cut-off values for deep MI in various studies, indicating that in endometrial cancer, the depth of MI has various roles according to the severity of the disease. In previous studies MI has been associated with certain biochemical indicators, including levels of free insulin-like growth factor-1 plasma (27), nucleoporin (88kDa)-mRNA expression (28) and endoplasmic reticulum-β (29). An association was also demonstrated between tumor-associated macrophages and depth of MI (30).…”
Section: A B Cmentioning
confidence: 87%
“…Interestingly, the ER-ß/ER-· mRNA ratio was high in advanced invasive carcinoma. Additionally, Western blot analysis demonstrated that ER-ß was highly expressed in comparison with ER-· in endometrial cancer with severe myometrial invasion, suggesting that ER-ß is important in the progression of myometrial invasion (19).…”
Section: Discussionmentioning
confidence: 97%
“…The loss of ER-ß expression in cancer cells might be a characteristic step in tumor cell dedifferentiation (13). Moreover, an imbalance in the ER-· and ER-ß expression might be of substantial importance in estrogendependent carcinogenesis (13,14,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A decreased ERα/ERβ ratio has been found to be associated with ovarian invasion in a large study comprising 214 endometrial carcinoma samples [65]. Low ERα/ERβ ratios have also been suggested to lead to progression of myometrial invasion [57,64,66]. Another study of 315 endometrial adenocarcinoma patients showed a decreased ERα/ERβ ratio to be associated with shorter DFS and OS [63].…”
Section: Erβ In Endometrial Cancermentioning
confidence: 99%